1984
DOI: 10.1111/j.1471-0307.1984.tb01241.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid determination of yeast numbers by impedance measurement using a Bactometer 32

Abstract: Yeasts can be detected by the Bactometer 32 both in broth and in broth containing 10% yogurt culture. Several broths gave results which agreed well with the colony count. and Malt Extract broth incorporating 2% glucose was selected as satisfactory. With yogurt it was necessary to include antibiotic (20 ppm chloramphenico[) in the broth to suppress the bacterial signals and allow good detection of the yeasts. Results were available three days earlier than for a colony count, even with a yeast of slow multiplic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Although work by Shapton & Cooper (1984) had shown that Malt Extract broth (MEB) with 2% glucose was satisfactory in the Bactometer B32, yeast glucose peptone broth (YGPB) gave equivalent results, and preliminary experiments using the M120B showed that MEB gave longer detection times than did YGPB. YGPB was therefore compared with carbon base ammonium sulphate broth (CBAS), which is recommended for yeast work in the M120B.…”
Section: Mediamentioning
confidence: 99%
“…Although work by Shapton & Cooper (1984) had shown that Malt Extract broth (MEB) with 2% glucose was satisfactory in the Bactometer B32, yeast glucose peptone broth (YGPB) gave equivalent results, and preliminary experiments using the M120B showed that MEB gave longer detection times than did YGPB. YGPB was therefore compared with carbon base ammonium sulphate broth (CBAS), which is recommended for yeast work in the M120B.…”
Section: Mediamentioning
confidence: 99%